2005
DOI: 10.1364/opex.13.004645
|View full text |Cite
|
Sign up to set email alerts
|

Light modulation with electro-optic polymer-based resonant grating waveguide structures

Abstract: A novel modulator design incorporating an E-O polymer into a resonant grating waveguide structure is presented. Using purely polymeric material we developed a resonant grating waveguide structure having low loss and high finesse, with approximately 2nm spectral line width at 1.55 mum. An externally applied voltage modulates the refractive index of the E-O waveguide, thereby shifting the resonance wavelength and modulating the incident light at MHz rates. Such modulator operates in free space and does not invol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
24
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 55 publications
(25 citation statements)
references
References 12 publications
0
24
0
Order By: Relevance
“…A similar tuning range has been demonstrated using thermally tuned SRG [12]. By incorporating the electro-optic polymer DR1 into a resonant grating structure, an optical modulator was demonstrated [13]. To dramatically increase the tuning range, the use of liquid crystal is attractive as it has, with proper anchoring, some of the largest known electro-optic coefficients.…”
Section: Introductionmentioning
confidence: 85%
“…A similar tuning range has been demonstrated using thermally tuned SRG [12]. By incorporating the electro-optic polymer DR1 into a resonant grating structure, an optical modulator was demonstrated [13]. To dramatically increase the tuning range, the use of liquid crystal is attractive as it has, with proper anchoring, some of the largest known electro-optic coefficients.…”
Section: Introductionmentioning
confidence: 85%
“…Only a few studies are reported on guided-mode resonance filters including an active layer [electro-optic (E-O), magneto-optic, etc.] [6][7][8]. They focus on the tunability performances in some configurations without a detailed analysis aiming at improving the tunability and other important properties, such as angular tolerance and polarization independence.…”
Section: Introductionmentioning
confidence: 99%
“…1, thus allowing wavelength-tunable filters, optical modulators, and reconfigurable OADMs to be realized. Wavelength tuning can be accomplished by varying the grating period [13], the angle of incidence [14], or the index of refraction of the grating [15] or an adjacent layer [16]. We have chosen to investigate the latter approach, in which the resonance wavelength is controlled by varying the refractive index of the superstrate medium (n 1 ).…”
Section: Introductionmentioning
confidence: 99%